(untitled) (Journal of the College of Basic Education, 2023)
The research aims to "recognize the evaluation methods used in evaluating art education in the middle school", and to achieve the goal of the research, the researcher used the descriptive approach. , which amounted to (30) teachers and schools (16) teachers and (14) schools. As for the research tool, the researcher prepared a list of evaluation methods that included (35) paragraphs distributed in seven main areas:- (performance-based evaluation, business files “portfolio” Self-evaluation, peer evaluation, observation-based performance evaluation, performance evaluation with interviews, and “oral and written” cognitive tests. , 2, 1) for each alternative, respectively, the apparent validity and reliability of the questionnaire were verified, and the results showed the weakness of the use of evaluation methods by teachers in the intermediate stage, with the difficulty of conducting some evaluation methods in the middle stage due to the lack of time and preparation Students with poor financial capabilities and lack of teachers’ experience. In light of this, the researcher came up with a set of recommendations and suggestions